‘Dreaming New Visions’: Indigenous Thinkers on Decolonising Education - Caroline Bagelman (Educational Futures, 2020)
De-colonial thinking and action must grapple with the antithetical nature of education: that it has the potential to both liberate and oppress. In the Canadian context, for instance, settler society used residential schools in the assimilationist mission to ‘kill the Indian’ in the Indigenous child, and education is now considered by Indigenous leaders as a site for building more than just relations (TRC, 2012; Donald, 2011). This article turns close attention to two Indigenous theorists to think through this tension: Linda Tuhiwei Smith, and Sandy Grande, who have been selected due to their importance in this field. Their work is particularly valuable due to their ability to identify and critique some core traits of colonial power that have been felt across continents and borders in different colonial contexts (meaning they have influenced leading scholars and practitioners internationally) (Denzin & Lincoln, 2011). While Smith’s work considers research methods, and how they take shape within higher education, to examine and inform research design and ethics, the focus of this paper is on the implications of her arguments for education and pedagogy specifically (Smith, 2012). Grande’s work looks explicitly at education, and within a cultural and historical backdrop distinct from Smith’s: Indigenous peoples and schooling in America (Grande, 2015). This article advances that in positioning these theorists together, it is possible to see key themes emerge across different contexts. In particular, it illuminates how colonisation operates through epistemic violence articulated and reproduced through education, and how making space for subjugated knowledges through education is a key step in decolonisation. Crucially, it is suggested in this paper, this must involve pedagogical shifts that reflect the subjugated knowledges of colonised peoples, and not simply curricular nods to their cultures, histories and experiences.